Do sports analytics affect footballer pay? - Butler, David; Farnell, Alex; Simmons, Robert (Frontiers in Behavioral Economics, 2024)
Labor economists aspire to understand how workers' productivity impacts pay. While professional football is a well-established domain to explore this relationship, so far, research has relied on basic productivity measures. Football is now awash with advanced and granular performance metrics that can allow a deeper understanding of the pay-performance relationship. We specify a salary model considering the newly available data and use sophisticated performance measures to explain contracted salaries in the English Premier League and Italian Serie A. We make a methodological breakthrough by identifying a sample of players who are in the first year of a new contract only. This results in a much tighter relationship between pay and performance. We estimate different salary equations using both basic and advanced performance statistics. Our main findings are, first, that few of our advanced performance metrics help to explain player salary and, second, that there is misalignment between individual performance determinants of team points and player salaries. JEL codes J41, Z22